Instagram Ads Usage to Increase Interest of Generation Z House Buying of PT Wengga Citra Jaya in East Kotawaringin - Viananda, Werra Triokta; Muharman, Deddy (Ilomata International Journal of Management, 2024)
Social media has become a digital platform for carrying out marketing activities. One of the social media used to carry out marketing activities is Instagram through the Instagram Ads feature. With a wise advertising strategy and utilizing existing features, Instagram Ads can be a very effective tool in influencing consumer buying interest and driving business growth. This research aims to analyze the use of Instagram Ads in an effort to increase interest in buying a house from PT Wengga Citra Jaya in East Kotawaringin Regency among generation Z. Generation Z's interest in buying a house is still relatively low due to several reasons and considerations. Generation Z are potential buyers in the future, so the low buying interest in generation Z must be overcome by carrying out marketing communication activities. This research uses qualitative method by collecting data through interviews with sources who are responsible for PT Wengga Citra Jaya's marketing activities and interviews with experts. The results of this research show that the efforts to use Instagram Ads carried out by PT Wengga Citra Jaya have not been optimal because there are elements that have not been used optimally. For maximum use, Instagram Ads must have information, images, audio, price and promotional elements. This research can be a reference for business actors who want to take advantage from Instagram Ads. To support maximum use of Instagram Ads, the supporting elements of the Instagram Ads should be maximally utilized to get more optimal results.